Comparison of therapeutic effects of continuous epidural nerve block combined with drugs on postherpetic neuralgia. (1st February 2021) - Dong, Xi'an; Liu, Yuantao; Yang, Qianqian; Liu, Zhaobin; Zhang, Zipu
Abstract: Purpose: To compare the therapeutic effects of continuous epidural block combined with drugs and oral drugs alone on postherpetic neuralgia (PHN). Methods: Ninety-six PHN patients meeting the standard were selected and divided into group A and group B. Patients in group A had epidural block combined with oral administration of gabapentin and oxycodone-acetaminophen, and patients in group B received oral gabapentin and oxycodone-acetaminophen. Visual analogue scale (VAS) and Wisconsin brief pain inventory scores were used to evaluate the patients in group A and group B for 6 times (before treatment, 1 d, 3 d, 7 d, 15 d and 30 d after treatment) respectively, and the complications and adverse reactions of the two treatment methods, as well as the number of cases requiring remedial measures were observed. Results: There were significant differences in VAS and Wisconsin brief pain inventory scores at 1 d, 3 d, 7 d, 15 d and 30 d after treatment between the two groups ( p < 0.05). Moreover, the scores before and after treatment decreased with the time of treatment, and there was a significant difference between the two groups at different time points ( p < 0.05). No significant adverse reactions were observed in group A except for 1 patient with catheter detachment. Compared with group A, the adverse reactions of group B were more varied and obvious. Conclusion: Both treatments have certain effects on PHN, but epidural block combined with drug therapy is more effective, especially for patients with severe pain, early use can quickly relieve pain.